2013
DOI: 10.1039/c3cy00209h
|View full text |Cite
|
Sign up to set email alerts
|

Novel ruthenium–terpyridyl complex for direct oxidation of amines to nitriles

Abstract: High catalytic activity and selectivity has been demonstrated for the oxidation of both aliphatic and aromatic amines to nitriles under benign conditions with dioxygen or air using the Ru 2 Cl 4 (az-tpy) 2 complex. The conversion was found to be strongly influenced by the alkyl chain length of the reactant with shorter chain amines found to have lower conversions than those with longer chains. Importantly, by using the ruthenium terpyridine complex functionalized with azulenyl moiety at the 4 position of centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…[21][22][23][24] For example, James et al reported the synthesis of a ruthenium-porphyrin complex that exhibited 100% selectivity under mild conditions (50°C, <16 h). 21 Later on Parvulescu introduced a faster novel ruthenium-terpyridyl complex that showed conversion of amines to nitriles after 2 h when using 5 atm of oxygen at 60°C, 25 while Maiti and co-workers developed new ruthenium hydrido complexes for the selective generation of nitriles and imines by varying the catalyst instead of the substrates. 26 More recently, different N-chelated ruthenium complexes [27][28][29] as well as simple [Ru(arene)Cl 2 ] 2 complexes have been demonstrated to be highly competent in amine dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] For example, James et al reported the synthesis of a ruthenium-porphyrin complex that exhibited 100% selectivity under mild conditions (50°C, <16 h). 21 Later on Parvulescu introduced a faster novel ruthenium-terpyridyl complex that showed conversion of amines to nitriles after 2 h when using 5 atm of oxygen at 60°C, 25 while Maiti and co-workers developed new ruthenium hydrido complexes for the selective generation of nitriles and imines by varying the catalyst instead of the substrates. 26 More recently, different N-chelated ruthenium complexes [27][28][29] as well as simple [Ru(arene)Cl 2 ] 2 complexes have been demonstrated to be highly competent in amine dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous heterogeneous ruthenium systems have also been reported for the production of nitriles and imines. [48][49][50][55][56][57][58][59][60] Kaneda et al reported am onomeric Ru 3 + species bound to ah ydroxyapatite surface (Ru/HAP), which acts as an efficient catalyst for the aerobic oxidationo fp rimary amines to nitriles (entry 1, Ta ble 3). [48] It showed ag ood functional group tolerance, and both aromatic and aliphatic amines were oxidizedu nder mild reactionc onditions in the presence of molecular oxygen as the sole oxidant.…”
Section: Nitriles and Iminesmentioning
confidence: 99%
“…Recently,P arvulescu and co-workers demonstrated the oxidation of aliphatic and aromatic amines in air by using ah omogeneous ruthenium-terpyridyl complex. [56] They showed that the dinuclearr utheniumc atalyst functionalized with an azulenylm oiety at the 4-position of the central pyridine core provided am uch highera ctivity of the catalysti nc omparison to as eries of other ruthenium-terpyridine-based complexes reported. Additionally,astrong dependence on the alkyl chain length of the reactantw as observed with respectt ot he conversion.…”
Section: Nitriles and Iminesmentioning
confidence: 99%
“…The catalytic activity of the complex [(tpy)Rh(OH)(H 2 O) 2 ] (NO 3 ) 2 in the oxidation of triphenylphosphine to triphenylphosphine oxide by the action of atmospheric oxygen was studied in [15]. Binuclear complex (LRuCl) 2 Cl 2 (L = 4 0 -azulenyl, 2,2 0 :6 0 ,2 00 -terpyridine) catalyzes the oxidation of amines to nitriles under the presence of oxygen or air into the autoclave [16]. Mono-tpy ruthenium and rhodium complexes with the additional bidentate ligands most commonly reported in the literature as catalysts.…”
Section: Introductionmentioning
confidence: 99%